Endoscopic ultrasound‐guided gallbladder and bile duct drainage with lumen apposing metal stent: A large multicenter cohort (with videos). Issue 1 (7th October 2021) - Rajadurai, Anton; Zorron Cheng Tao Pu, Leonardo; Cameron, Rees; Tagkalidis, Peter; Holt, Bronte; Bassan, Milan; Gupta, Saurabh; Croagh, Daniel; Swan, Michael; Saxena, Payal; Efthymiou, Marios; Vaughan, Rhys; et al.
Abstract: Background and Aim: Cholecystectomy and endoscopic retrograde cholangiopancreatography are the gold standard for managing acute cholecystitis and malignant biliary obstruction, respectively. Recent advances in therapeutic endoscopic ultrasound (EUS) have provided alternatives for managing patients in whom these approaches fail, namely, EUS‐guided gallbladder drainage (EUS‐GB) and EUS‐guided bile duct drainage (EUS‐BD). We aimed to assess the technical and clinical success of these techniques in the largest multicenter cohort published to date. Methods: A retrospective, multicenter, observational study involving 17 centers across Australia and New Zealand was conducted. All patients who had EUS‐GB or EUS‐BD performed in a participating center using a lumen apposing metal stent between 2016 and 2020 were included. Primary outcome was technical success, defined as intra‐procedural successful drainage. Secondary outcomes included clinical success and 30‐day mortality. Results: One hundred and fifteen patients underwent EUS‐GB ( n = 49) or EUS‐BD ( n = 66). EUS‐GB was technically successful in 47 (95.9%) while EUS‐BD was successful in 60 (90.9%). All failed cases were due to maldeployment of the distal flange outside of the targeted lumen. Clinical success of EUS‐GB was achieved in 39 (79.6%). No patients required subsequent cholecystectomy. Clinical success of EUS‐BD was achieved in 52 (78.8 %). Thirty‐day mortality was 14.3% for EUS‐GB and 12.1% for EUS‐BD. Conclusions: EUS‐guided gallbladder drainage and EUS‐BD are promising alternatives for managing nonsurgical candidates with cholecystitis and malignant biliary obstruction following failed endoscopic retrograde pancreatography. Both techniques delivered high technical success with acceptable clinical success. Further research is needed to investigate the gap between technical and clinical success.